Conversations across time and space: classical traditions in the andes (2001)
On a June night in 1557,Gonzalo Fernández de Oviedo, courtier, soldier, imperial official, man of letters and historian, lay on his deathbed, clasping in his hands the key to the fortress of Santo Domingo of which he had been commandant, alcaide, during the preceding thirty four years. 2 His life had been long and event ful. In his youth, he had served in the household of the Infante Don Juan, son of Ferdinand and Isabel, at whose side he witnessed the capture of Granada. After the lnfante's premature death in 1498, Oviedo spent some time in Italy. Long afterwards, he was still exchanging letters with some of the eminent Italians whom he had met during those years.